Draft Tribal Sub Plan Bihar (Non-Transferred Sectors) Vol-II 1988-89 - Planning Commission (Planning Commission, 1987)
Land Reforms measures form an integral part of the plan strategy and are implemented with a view to removing impediments existing in the present agrarian system. For strengthening and developing the predominantly agricultural economy of the State a proper implementation of Land Reforms Acts and Regulations is a pre-requisite.
Government of Bihar